No sense of place - Meyrowitz, Joshua (Oxford University Press, 1986)
How has television affected our everyday experience? This question has generated endless arguments and speculations, but no thinker has addressed the issue with such force and originality as Joshua Meyrowitz in No Sense of Place. Advancing a daring and sophisticated theory, Meyrowitz shows how television and other electronic media create new social situations that are no longer shaped by where we are or who is "with" us.